Evaluation of cross curves of fishing vessels at the preliminary design stage - Yilmaz, H; Kükner, A (PERGAMON-ELSEVIER SCIENCE LTD, 1999)
The prediction of ship stability during the early stages of the design process is very important from the point of a vessel's safety. Hence, in this study, a formula is presented to estimate cross curves of fishing vessels to predict initial stability at the preliminary design stage. For this purpose, 175 fishing vessel forms have been generated from Doust trawler hull series. The predictive technique is established by regression analysis of systematically varied fishing vessel series data. The mathematical model is constructed as a function of main design parameters such as length to beam ratio L-WL/B-WL, beam to draft ratio B-WLT, moulded depth to draft ratio D/T and block coefficient C-B This prediction is also used to determine the effect of specific hull form parameters and load conditions on the stability of the fishing vessel. Some basic considerations on how the proposed method can be applied to a new fishing vessel are presented. (C) 1999 Elsevier Science Ltd. All rights reserved.
Keywords: fishing vessel; cross curves; stability; preliminary design; Engineering; Oceanography